ГІДНІСТЬ: ФЕНОМЕНОЛОГІЯ ТА ОСОБЛИВОСТІ РОЗВИТКУ У ДОШКІЛЬНОМУ ДИТИНСТВІ - Кононко, О. Л. (My University, 2022)
Розкрито суть феномену «власна гідність», який кваліфіковано як особистісний інтеграл, показник прогресивного розвитку, що засвідчується активною за формою та моральною за змістом життєвою позицією дитини дошкільного віку, умінням конструктивно реалізовувати свій потенціал, поводитися самостійно й впевнено, досягати успіху у чесний спосіб, аргументувати незгоду та коректно відстоювати власну точку зору у спілкуванні з оточуючими людьми. Визначено критерії оцінки міри та особливостей розвитку гідності дітей 5–7 років, основ- ними з яких слугували такі уміння: самовиражатися та самореалізовуватися у соціально прийнятний спосіб; довіряти власному досвіду, підтримувати себе у складній ситуації; відстоювати простір-Я, чинити опір руйнівним впливам. Описано авторську типологію гідності, схарактеризовано особливості свідо- мості та поведінки самодостатніх, самолюбних, егоцентричних та індиферент- них дітей. Обгрунтовано педагогічні умови оптимізації виховного процесу у закладі дошкільної освіти з метою розвитку в дітей 5–7 років елементарних форм власної гідності. До них віднесено: збагачення уявлень дошкільників про гідність та її роль в житті; формування інтересу до власної особистості та самоаналізу; розширення інструментарію самовпливу, саморегуляції та самокон- тролю; створення ситуацій успіху, вправляння дітей в в уміннях аргументувати та відстоювати власну думку.
The introduction of a personally oriented paradigm into pedagogical practice actualizes the need for an in-depth study of the phenomenon of dignity, which is evidenced by the progressive personal growth of a child. An excursion into the psychological and pedagogical literature gives reasons to state the lack of theoretical and experimental domestic research devoted to the study of dignity as an important and complex personal phenomenon. This especially applies to early ontogenesis, when the foundations of selfawareness in general, such as its emotional and value component, such as self-attitude, are laid. It is time to clarify the content of the leading category, develop criteria for assessing the degree and features of the development of dignity at the stage of preschool childhood, create a typology of dignified behavior of a child of 5-7 years of age, substantiate the pedagogical conditions for optimizing the educational process in the family and preschool education institution. The purpose of the article: clarifying the content and structure of dignity as an integral characteristic of the personality, determining the criteria and indicators of its development in a child of older preschool age, characterizing the types of dignity and the conditions for optimizing the educational process aimed at developing the self-esteem of a 5-7-year-old child in the family and preschool institution education Methods: analysis and generalization of data of philosophical and psychological – pedagogical literature on the researched problem; theoretical modeling for construction of diagnostic research methods; observations, individual conversations. The results. The main results of the study include: a) the interpretation of dignified behavior as corresponding to a high level of personality development, adequate to life challenges, important for self-realization and progressive development of the "I"; b) definition of dignity as a basic personality quality, which is manifested in a respectful attitude towards oneself, self-esteem, independent and confident behavior, sincerity and adequacy of self-evaluation judgments, ability to argue and defend one’s position, striving to show and develop the best qualities in oneself; c) development of criteria assessment of the peculiarities of the development of dignity in preschool age, which were demonstrated by a complex of skills: to realize one’s natural and acquired abilities, to support oneself in difficult and stressful situations, to provide oneself with a safe personal space; d) development of the author’s typology of dignity, which unites and characterizes such behavior strategies typical for children of 5-7 years as self-sufficient, self-loving, egocentric and indifferent; e) substantiation of pedagogical conditions for optimizing the educational process in a preschool education institution, the most important of which were: enrichment of preschoolers’ ideas about healthy dignity and its importance for a successful life; the formation of self-interest, the ability to analyze one’s actions, qualities, achievements and evaluate them adequately; training in the ability to constructively influence oneself, control and regulate behavior and emotions; providing an opportunity to assert oneself in socially approved and acceptable ways, to achieve success in activities. Originality. For the first time: the subject of pedagogical research was the dignity of an older preschool child as a personal phenomenon, which is evidenced by his ability to realize his natural potential in the best way, instrumentally and emotionally support himself in a difficult situation, create a safe personal space and defend his right to it. The completeness and degree of formation of the specified skills served as criteria for evaluating the peculiarities of the development of self-esteem in children aged 5-7 years. The author’s typology of the studied phenomenon is substantiated and characterized, and four types of behavior of preschoolers in situations of moral choice are distinguished – self-sufficient, selfish, egocentric and indifferent. Pedagogical conditions for optimizing the educational process in a preschool education institution, aimed at fostering a sense of self-worth as a personal integral, have been determined. Conclusions. A shortage of domestic studies focused on the peculiarities of the development of dignity in early ontogeny was recorded. The relevance of the problem of raising self-esteem among children of older preschool age as the ability to realize their own capabilities in socially approved and acceptable ways, to support themselves in situations of encountering difficulties, to show independence and confidence in their own abilities, to control and regulate behavior and emotional state, to defend the space- I and 57 personal position. The criteria for evaluating the peculiarities of upbringing in older preschool children’s self-esteem were: the ability to realize one’s natural and life-acquired potential; the ability to instrumentally and emotionally support oneself in a difficult situation; the ability to create a safe personal space, to defend one’s position, to resist external destructive influences. The types of behavior of preschoolers in difficult situations are characterized: self-sufficient, selfish, egocentric and indifferent. The conditions for optimizing the educational process aimed at the development of dignity in children aged 5–7 years as a basic personality quality are recognized as: enriching ideas about the meaning and role of dignity in life, practicing the ability to support oneself in a difficult situation, constructively influence behavior and emotions, control and to regulate their actions and deeds; correctly defend your rights, position, personal space.
Keywords: сутнісні внутрішні сили; гідність; самоповага; ціннісне само ставлення; самореалізація; саморозвиток; самозахист; мотивація длосягнення; оптимізація виховного процесу